In vitro and in vivo anti-cancer activity of tangeretin against colorectal cancer was enhanced by emulsion-based delivery system. (May 2015) - Ting, Yuwen; Chiou, Yi-Shiou; Pan, Min-Hsiung; Ho, Chi-Tang; Huang, Qingrong
Highlights: The emulsion system enhanced the anti-cancer efficacy of tangeretin. The proliferation of colon carcinoma cells was better inhibited by emulsified tangeretin. Tumour incidence and multiplicity were significantly reduced by emulsified tangeretin. The emulsion reduced the inflammation and proliferation related protein expression. The first successful use of nutraceuticals oral formulation on long-term animal model. Abstract: The oral bioavailability and efficacy of citrus polymethoxyflavone, tangeretin, was attenuated by its poor aqueous solubility. An emulsion-based delivery system was utilized to enhance the anti-tumourigenesis activity of tangeretin. The in vitro anti-proliferative activity of tangeretin was first evaluated using methyl thiazol tetrazolium bromide (MTT) test on colonic carcinoma cell lines, HCT116 and HT29. The utilization of emulsion system significantly improved the efficacy of tangeretin at dosing concentrations at 12.5 and 25 µM. The effectiveness of the emulsion system in enhancing the in vivo oral efficacy of tangeretin against colorectal cancer development was also evaluated by azoxymethane/dextran sodium sulphate (AOM/DSS)-induced colitis related colon tumourigenesis model. The tumour incidence, multiplicity, and pathological signs of colorectal adenoma were significantly reduced when tangeretin emulsion was applied. The regulation on tumourigenesis related protein expression was more effective in mice treated with tangeretin emulsion than unformulated suspension. Our finding indicated that emulsion-based delivery system was an effective means to increase the oral efficacy of tangeretin. This study is the first successful demonstration of the effect of delivery system on the oral efficacy of nutraceutical using long-term animal model.